2018
DOI: 10.2478/prolas-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics Content in Buckwheat Flour

Abstract: The objective of the current study was to analyse the total phenolic concentration (TPC), total flavonoid concentration (TFC), individual phenolic compound concentration and DPPH′ radical scavenging activity of four buckwheat (raw, roasted, white and dark) flour samples obtained from the Latvian market, in comparison to those of wheat flour, which is the most common ingredient in production of cereal products. TPC, TFC, and DPPH′ radical scavenging activity values were determined using spectrophotometric metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
2
8
0
1
Order By: Relevance
“…The findings are in close conformity with the results of (Cao et al, 2008), who reported that Tartary buckwheat contained a higher quantity of antioxidant capacity as compared to common buckwheat wheat. The findings are also consistent with those of (Beitāne et al, 2018), who discovered that the buckwheat flour samples contained DPPH scavenging activity ranging from 21.067 to 22.644 mM TE 100 g -1 dry matter. The buckwheat sample contained higher DPPH radical scavenging activity as compared to wheat flour, and the total antioxidant activity ranged from 25.61 mM TE 100 g -1 DM for white buckwheat flour to 27.17 mM TE100 g -1 DM for raw buckwheat flour (Guo et al, 2011).…”
Section: Total Antioxidant Activitysupporting
confidence: 91%
See 1 more Smart Citation
“…The findings are in close conformity with the results of (Cao et al, 2008), who reported that Tartary buckwheat contained a higher quantity of antioxidant capacity as compared to common buckwheat wheat. The findings are also consistent with those of (Beitāne et al, 2018), who discovered that the buckwheat flour samples contained DPPH scavenging activity ranging from 21.067 to 22.644 mM TE 100 g -1 dry matter. The buckwheat sample contained higher DPPH radical scavenging activity as compared to wheat flour, and the total antioxidant activity ranged from 25.61 mM TE 100 g -1 DM for white buckwheat flour to 27.17 mM TE100 g -1 DM for raw buckwheat flour (Guo et al, 2011).…”
Section: Total Antioxidant Activitysupporting
confidence: 91%
“…Our results are closely in conformity with the findings of (Izydorczyk et al, 2014), who reported that the Tartary buckwheat contained a higher quantity of total phenolic content as compared to the common ones. All buckwheat samples had a higher total phenolic content than wheat flour and the highest total phenolic content (974.74 mg GAE/100 g DW) was observed in raw buckwheat flour (Beitāne et al, 2018). Tartary buckwheat contained two times higher amounts of total phenolic than common buckwheat.…”
Section: Total Phenolic Contentmentioning
confidence: 89%
“…In terms of the thermal effects on phenolic profiles and antioxidant capacities in the common buckwheat sample, some notable increases in certain phenolic acids were observed in the present study. For example, the content of gallic acid was increased markedly (+239.1%) after the roasting treatment, which was in good agreement with the results of a study by Beitāne et al ., who reported that the roasting treatment gave rise to a 36% higher gallic acid content compared to raw buckwheat flour. In addition, all four thermal treatments, particularly the roasting treatment, led to a 3.56‐fold higher syringic acid content in the common buckwheat seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing our results with other authors, Beitâne et al [61] performed a study about phenolics content in buckwheat flour and also identified luteolin and gallic acid, but not syriginc acid. On the other hand, Jubete et al [62] identified luteolin and syriginc acid in buckwheat seeds, but not gallic acid. In both studies, rutin was identified in buckwheat; however, in our study, this flavonol was not detected in the control bread, where the buckwheat flour level was higher, with a 43% share.…”
Section: Control A23% A35%mentioning
confidence: 97%